Makna Syifa' dalam Al Qur'an Perspektif Tafsir Al Azhar - Salma Nugrahani Nur Indahsari; Abdullah Mahmud (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The Qur'an serves as a source of spiritual healing and inner peace, effectively addressing various psychological ailments. This study aims to explore the interpretation of syifa’ in the Qur'an from the perspective of Tafsir Al-Azhar. The research method used in this study is a library research approach. The findings indicate that the concept of syifa’ in the Qur'an is not limited to physical healing but also encompasses mental and spiritual well-being. Implementing the moral values embedded in these verses can be an effective solution to overcoming feelings of insecurity and fostering a more balanced and faith-driven life.